Impact of SARS-CoV-2 on pregnancy and neonatal outcomes: An open prospective study of pregnant women in Brazil (Clinics, 2022)
Objectives: To determine the incidence and risk of adverse obstetric and neonatal outcomes according to SARS-CoV-2 infection severity in pregnant women.Method: Open prospective study of pregnant women tested for SARS-CoV-2 by serological and molecular assays during pregnancy or delivery in two hospitals in Sao Paulo, Brazil from April 12, 2020, to February 28, 2021. Five groups were considered for analysis: C0, negative COVID-19 results and no COVID-19 symptoms; C1, positive COVID-19 results, and no symptoms; C2, positive COVID-19 results with mild symptoms; C3, positive COVID-19 results with moderate symptoms; and C4, positive COVID-19 results with severe symptoms. The association between obstetric and neonatal outcomes and COVID-19 severity was determined using multivariate analysis.Results: 734 eligible pregnant women were enrolled as follows: C0 (n = 357), C1 (n = 127), C2 (n = 174), C3 (n = 37), and C4 (n = 39). The following pregnancy and neonatal outcomes were associated with severe COVID-19: oligohydramnios (adjusted Odds Ratio [aOR] = 6.18; 95% CI 1.87‒20.39), fetal distress (aOR = 4.01; 95% Confidence Interval [CI] 1.84‒8.75), preterm birth (aOR = 5.51; 95% CI 1.47‒20.61), longer hospital stay (aOR = 1.66; 95% CI 1.36‒2.02), and admission to the neonatal intensive care unit (aOR = 19.36; 95% CI, 5.86‒63.99). All maternal (n = 6, 15.4%, p < 0.001) and neonatal (n = 5, 12.5%, p < 0.001) deaths and most fetal deaths (n = 4, 9.8%, p < 0.001) occurred in C4 group. Moderate COVID-19 was associated with oligohydramnios (aOR = 6.23; 95% CI 1.93‒20.13) and preterm birth (aOR = 3.60; 95% CI 1.45‒9.27). Mild COVID-19 was associated with oligohydramnios (aOR = 3.77; 95% CI 1.56‒9.07).Conclusion: Adverse pregnancy and neonatal outcomes were associated with maternal symptomatic COVID-19 status, and risk increased with disease severity.